Structural and Physical Properies of Y- doped BiFeO3 Material Prepared by Sol-gel Method - Thang, Dao Viet; Thao, Du Thi Xuan; Minh, Nguyen Van (VNU Journal of Science: Mathematics - Physics; Vol 29 No 3, 2013)
Abstract: Y - doped BiFeO 3 materials were prepared by a sol – gel method. X-ray diffraction (XRD) meansurement has been carried out to characterize crystal structure and to detect the impurities existing in these materials. The results showed that both lattice constants a and c of the unit cell of BiFeO 3 substance become smaller as the Y 3+ content is increased. The effect of introducing Y 3+ was to decrease the optical band gap for doped samples Bi 1−x Y x FeO 3 (x = 0.00   QUOTE    0.20). Magnetic properties of Y-doped BiFeO 3 were investigated by vibrating sample magnetometer (VSM) measurements at room temperature, using maximum magnetic field of about 10 kOe. T hese materials exhibited a weak ferromagnetic behavior and magnetization of the  sample was improved as presence of  Y 3+ ions. When x = 0.15, 0.20 , structural and magnetic properties change sharply . Y doping BiFeO 3 material modifies its physical properties.